Fundamentals of Entrepreneurship (ENT 300) : Case Study Apparels Business / Patrick Sullang Ambun ... [et al.] - Ambun, Patrick Sullang; Jai, Azwan; Coilven, Jeff (2011)
Lea Sport Centre, is formed by the Lea Group of Companies since 22 April 1994. The retail store is focusing on selling high-performance sportswear products such as Adidas brand, Nike brand, and Puma brand, which is widely known globally. One of the Lea Sport Centre stores is located at The Summer Shopping Mall - Kota Samarahan. We have made an interview with the store’s supervisor. During the interview, we were talking about the background company that has succeed in business that was incorporated since 1994 until now. As the interview gone by, the supervisor applied a lot of knowledge in term of business especially when it involves with sports products. The ideas the company obtained literally from the current world sport situation, where young generations mostly show they interest in sports.